2002
DOI: 10.1097/00001648-200207000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Improved Air Quality in Reunified Germany and Decreases in Respiratory Symptoms

Abstract: The decreasing prevalence of nonallergic respiratory symptoms, along with improvements in ambient particle mass and sulfur dioxide (but not in nucleation-mode particles), indicates the reversibility of adverse health effects in children. This adds further evidence of a causal association between combustion-related air pollutants and childhood respiratory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 20 publications
6
84
1
7
Order By: Relevance
“…The annual mean TSP decreased from 1991 to 1998. The crude prevalence of bronchitis in the three respective areas decreased by 15%, 12%, and 11% between 1992 and 1995 [14]; prevalence of nonallergic respiratory symptoms also decreased for an extended follow-up until 1999, indicating the reversibility of adverse health effects [14,15]. This adds further evidence to a causal association between combustion-related air pollutants and childhood respiratory symptoms.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The annual mean TSP decreased from 1991 to 1998. The crude prevalence of bronchitis in the three respective areas decreased by 15%, 12%, and 11% between 1992 and 1995 [14]; prevalence of nonallergic respiratory symptoms also decreased for an extended follow-up until 1999, indicating the reversibility of adverse health effects [14,15]. This adds further evidence to a causal association between combustion-related air pollutants and childhood respiratory symptoms.…”
mentioning
confidence: 65%
“…One of these studies reported effect estimates stratified for children with and without indoor exposures such as those derived from parental tobacco smoke, emissions from gas stoves, mouldy or damp homes or from cats. Children without these indoor exposure revealed higher effect sizes and had a greater benefit from the improvement of air hygiene levels than children who were exposed to at least one of these indoor pollutants [15]. The effect size estimates for FVC were also higher in children not exposed to these indoor factors [47].…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the closure of several industries in Hettstedt and the convergence of particle mass levels during the 1990s, regional differences in PM elemental composition persist (Heinrich et al 2002a), perhaps as a result of the reopening of industries in Hettstedt, persisting industrial emissions, resuspension of contaminated dust from slagheap, and geographical characteristics of the region, as Hettstedt is in a valley surrounded by hills, whereas Zerbst is located in a fairly level county (Heinrich et al 1999(Heinrich et al , 2002a. Although Zerbst has a predominant agricultural economy, endotoxin levels present in both Zerbst and Hettstedt PM 2.5 samples were very low, indicating that endotoxin was not responsible for the observed enhancement of allergic airway responses.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that exposure to air pollutants, including PM 2.5 (PM < 2.5 µm aerodynamic diameter), could promote sensitization to common aeroallergens and promote the development or exacerbation of allergic and respiratory diseases. After German reunification, levels of total PM and sulfur dioxide in eastern Germany decreased throughout the 1990s, and regional differences in the prevalence of bronchitis, sinusitis, and frequent colds declined (Heinrich et al 2000(Heinrich et al , 2002a. However, the difference in the prevalence of allergies between the two cities continued, despite the convergence of ambient PM concentrations (Heinrich et al 2002b), suggesting that the composition of Hettstedt PM may also contribute to the higher prevalence of allergies in that area.…”
mentioning
confidence: 99%